Improving Awareness of HIV Prophylaxis Amongst Non-Healthcare Individuals: A Research Proposal (British Journal of Multidisciplinary and Advanced Studies, 2025)
The goal of ending the HIV epidemic by 2030, with the worldwide effort to address the HIV epidemic, is in line with Sustainable Development Goal (SDG) 3.3. Strategies have been put in place by WHO, UNAIDS, and the Global Fund to address the substantial financial and public health impact of HIV, especially in low- and middle-income countries. HIV infection continues to be a danger to quality of life despite continuous efforts. HIV prophylaxis, which includes both pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis (PEP), plays an important role in the fight against new infections. Although it is clear that these preventive measures are helpful, there are noticeable gaps in knowledge and adherence, especially among non-healthcare individuals. Although special attention should be given to HCW, it is also important also to focus on the general public.  For a complete strategy to HIV prevention, it is imperative to close gaps in public knowledge and improve awareness on HIV prophylaxis. The main aim of this research is to first investigate reasons why non-healthcare individuals have low awareness level of HIV prophylaxis both PREP and PEP and also evaluate ways to improve awareness and uptake by these category of individuals. This study will use a mixed-method approach to assess HIV prophylactic knowledge in Greater Accra, Ghana (PEP and PrEP). Surveys and interviews will be conducted with 200 participants in the research, which includes FSW, MSM, and hospital patients. Random sampling and snowballing are two techniques for sampling. Validity and reliability will be ensured through, thorough training of research assistants, pretesting research tools by pilot study.  For ethical principles, there would be Participant anonymity, informed consent, IRB compliance, and safe data processing. This   research proposal will go a long way by providing evidence-based knowledge to decision makers. The outcomes will guide the creation of community outreach initiatives, educational campaigns, and specialized medical services. By filling information gaps, identifying relationships, and advancing global health initiatives, the research hopes to improve public health outcomes through well-informed actions.